Intestinal inflammation modulates expression of 11beta-hydroxysteroid dehydrogenase in murine gut - Vagnerová, K; Kverka, M; Klusonová, P; Ergang, P; Miksík, I; Tlaskalová-Hogenová, H; Pácha, J (The Journal of endocrinology, 2006)
The effect of glucocorticoids is controlled at the pre-receptor level by the activity of 11beta-hydroxysteroid dehydrogenase (11HSD). The isoform 11HSD1 is an NADP+ -dependent oxidoreductase, usually reductase, that amplifies the action of glucocorticoids due to reduction of the biologically inactive 11-oxo derivatives cortisone and 11-dehydrocorticosterone to cortisol and corticosterone. The NAD+ -dependent isoform (11HSD2) is an oxidase that restrains the effect of hormones due to 11beta-oxidation of cortisol and corticosterone to their 11-oxo derivatives. Although the immunosuppressive and anti-inflammatory effects of glucocorticoids are well known, the relationship between inflammation and local metabolism of glucocorticoids is not well understood. In this study, we demonstrated that colitis induced by dextran sulfate sodium modulates colonic 11HSD1. Experimentally induced intestinal inflammation stimulated colonic NADP+ -dependent but not NAD+ -dependent 11HSD activity. Colonic 11HSD1 mRNA was increased, whereas 11HSD2 mRNA was not changed. Additional parallel studies revealed a similar pattern of 11HSD1 mRNA induction in mesenteric lymph nodes and intestinal intraepithelial lymphocytes, but not in spleen and peritoneal macrophages. These data suggest that inflammation modulates local metabolism of glucocorticoid and support the notion that pre-receptor regulation of endogenous corticosteroids might play a role in inflammatory processes.
Keywords: myši; aktivace enzymů; kolitida; Enzyme Activation; Animals; Colon; Dextran Sulfate; Mice; Models, Animal; kolon; Mice, Inbred BALB C; Female; síran dextranu; 11-beta-hydroxysteroiddehydrogenasy; ženské pohlaví; 11-beta-Hydroxysteroid Dehydrogenases; RNA, Messenger; modely u zvířat; myši inbrední BALB C; zvířata; Colitis; polymerázová řetězová reakce s reverzní transkripcí; Reverse Transcriptase Polymerase Chain Reaction; messenger RNA